Ovarian masses in children: A single center’s experience - Sonay Yalcin Comert, Hatice; Eyuboglu, Ilker; Ersoz, Safak; Akdogan, Ali; Imamoglu, Mustafa; Sarihan, Haluk (Annals of Medical Research, 2021)
Aim: Although ovarian masses are rare in children, they differ forevery age group. We aimed to evaluate the management of patients diagnosed with ovarian masses in our clinic. Material and Methods: The medical records of patients (age ≤ 18) who underwent operations for ovarian masses during the period 2009-2019were evaluated retrospectively. Demographic findings, presenting symptoms and signs, the results of radiological examinations, mass locations and sizes, tumor markers, histopathological diagnoses and cases’surgical intervention were recorded.Results: The study included 51 patients with a total of 54 surgical interventions. There was a significant difference between tumor size and pathological diagnosis (p0.048) between the pathological diagnosis and the surgical intervention for patients who required oophorectomy and did not require oophorectomy (p=0.02) and presenting symptoms and signs with pathological diagnoses (p=0.027). We found no difference in the patients’ age of presentation and the pathological diagnoses (ovarian torsion, neoplastic or non neoplastic lesions) (p=0.542). We also found no difference between tumor markers and pathological diagnoses (p=0.253 for CEA, p=0.345 for αFP and p=0.129 for βHCG) or mass location (right or left side) with the pathological diagnoses (p=0.246).Conclusion: : Ovary preservation surgery is important for ovarian masses in children, and we must be careful when performing surgery on these patients.